Business and the environment (Macmillan Press, 1995)
Proceedings of a workshop held in Seville, Spain (date not identified), organized by the Institute for Prospective Technological Studies, a specialized service of the European Commission. The aim of the workshop was to identify practical steps toward the improvement of industrial processes and products with a view to long-term sustainable development. The volume is divided into seven sections: international perspectives, environmental management, technology, case study<-->flue gas desulfurization, towards sustainability, the role of financial institutions, and the role of the regulators. Each section concludes with discussion highlights. Annotation c. by Book News, Inc., Portland, Or.